2021
DOI: 10.1002/cem.3342
|View full text |Cite
|
Sign up to set email alerts
|

Influence diagnostics in the inverse Gaussian ridge regression model: Applications in chemometrics

Abstract: The influential observation affects the regression model inferences. Literature has shown that the problems of multicollinearity and influential observations can jointly exist in a model. The ridge regression estimator has been developed to handle the challenge of multicollinearity. The detection of influential observations with multicollinearity and its impact on the ridge estimates is necessary for better decision making. In this article, we proposed some influence diagnostics for the inverse Gaussian ridge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Khan et al [35] assessed the performance of influence diagnostics in the PRM with a ridge estimator. Recently, Khan et al [36] examined the superiority of influence diagnostics in the PRM with two-parameter estimator and, further, Amin et al [37] discussed the influence diagnostics for the inverse Gaussian ridge regression model. e available literature showed that no study in the GLM is available for influence diagnostics with the Liu estimator.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [35] assessed the performance of influence diagnostics in the PRM with a ridge estimator. Recently, Khan et al [36] examined the superiority of influence diagnostics in the PRM with two-parameter estimator and, further, Amin et al [37] discussed the influence diagnostics for the inverse Gaussian ridge regression model. e available literature showed that no study in the GLM is available for influence diagnostics with the Liu estimator.…”
Section: Introductionmentioning
confidence: 99%